Elementos de política de indexação em biblioteca universitária da área médica - Redigolo, Franciele Marques [UNESP]; Dal' Evedove, Roberta Cristina; Fujita, Mariângela Spotti Lopes [UNESP]; Boccato, Vera Regina Casari [UNESP] (My University, 2012)
In the context of university libraries, the optimization and streamlining of services and processes related to informational content indexing and retrieval are strongly influenced by the indexing policy adopted. This article is aimed at researching the indexing policy elements that are more suitable for medical university libraries. To achieve our objective, we applied three instruments: organizational culture analysis, individual verbal protocol and evaluation of indexing. Results emphasize the importance of developing an indexing policy to improve the processes and services offered by university libraries, as well as the retrieval of information by the user community. More studies are necessary in the medical area involvoving catalogers, experts, users and managers for the development of the indexing manual.
Elements of indexing policy for medical academic libraries
Keywords: Assesment; Indexing; Indexing policy; Medicine; Organizational culture; University libraries; Verbal protocol